Governance and Local Development: The Problematique of the Concept (Journal of human and social sciences, 2023)
Referring to the concept of governance, we find that it has evolved in parallel with the evolution of the concept of development, especially when the focus shifted from economic growth to social capital and then to human development. Thus, governance is the guarantor of transforming economic growth into real and sustainable development, considering that the issue of development and the objectives of governance are the gateway to achieving economic and social well-being. This has made governance, in its developmental dimension, a fundamental pillar for enhancing decentralization and a key mechanism in promoting the developmental role of local communities in any country. Among the requirements of local development within the framework of good governance is working to mobilize all available potentials, resources, and energies in a specific local area, aiming to create and develop its productive activities, improve the standard of living for all its inhabitants, and replace centralization in planning, decision-making, and others with all the components of decentralization. Needless to say, the stakes of good governance in its relationship with local development are to push local democracy forward. This process will only be achieved by invoking indicators of local development, which include raising the level of education and awareness among the local population, improving their economic, social, and cultural conditions, in addition to strengthening the rule of law with institutions built on solid foundations that encourage the individual to participate in public life with full commitment and responsibility. Making the local community a basic geographical framework for producing sustainable local development can attract investment, revitalize employment, combat marginalization and social exclusion, and entrench democratic practice, constructive citizenship values, and effective participation of all components of the local community, while establishing the principle of accountability and oversight. Thus, governance as a tool for achieving development at the local level has been associated in political and economic discourse since its emergence as a new concept with local bodies, where it found in the local sphere a suitable ground to consolidate its foundations and a fertile field to test its priorities, draw its development plans, and set its economic and social strategies.
Keywords: Good Governance; Local Communities; Local Democracy; Accountability; Local Society